Конституційно-правовий механізм захисту суспільної моралі - Припхан, І. І.; Припхан, И. И.; Prypkhan, I. I. (Одеса : Юрид. л-ра, 2012)
The author has analysed maintenance and essence of constitutional and legal mechanism of defence of public morality and determined its component elements, has exposed the value of constitutional and legal guarantees in the sphere of defence of public morality in the given article.
Припхан І. І. Конституційно-правовий механізм захисту суспільної моралі / І. І. Припхан // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С.
Keywords: суспільна мораль; конституційно-правовий механізм; правовий захист; гарантії; общественная мораль; конституционно-правовой механизм; правовая защита; гарантии; public morality; constitutional and legal mechanism; legal protection; guarantees